Hydration behavior and formation of strätlingite compound (C2ASH8) in a bio-cement based on tri-calcium silicate and mono-calcium aluminate for dental applications: influence of curing medium - Radwan, M. M. (2023)
Evaluation of the final setting time was carried out on the material pastes of normal consistency prepared with distilled water at a liquid/solid ratio of 0.23 ml/g as given in “Setting time” section. The recorded average setting time was 20 min at 37 °C (average of five readings). Figure 3 shows the hardness data of samples cured in the different hydration media at all curing ages. Figure 3 indicates that the hardness values of samples cured in distilled water (DW) increase with the hydration period from one day and up to 14 days, while for samples cured in SBF solution and the Pseudomonas aeruginosa microbe in MHB media there was a decrease in the hardness values at all curing ages. However, the samples immersed in the microbe medium showed slightly higher hardness values than those cured in SBF solution at all hydration periods.